Does the Islamic Marketing Mix Model Matter in Coping with the Rising Cost of Living in Malaysia During the Crisis? - Mohammad Tahir Zainuddin; Muhamad Azrin Nazri; Nuradli Ridzwan Shah Mohd Dali; Nursilah Ahmad (Universal Publishers - Boca Raton, Florida, USA, 2024)
Indexed by ERA